Chronology, time averaging, and oxygen isotope composition of harvested marine mollusk assemblages from Ifri Oudadane, northeast Morocco. (March 2022) - Sanchez, William; Yanes, Yurena; Linstädter, Jörg; Hutterer, Rainer
Abstract: The archaeological site of Ifri Oudadane, NE Morocco, contains well-preserved marine mollusk concentrations throughout the Epipaleolithic (hunting-gathering) and Neolithic (food production) cultural phases, useful to test hypotheses driving such transition. However, the chronology and stratigraphy of harvested shells is complex due to the confluence of human activity and natural deposition processes. This work first quantifies the age and degree of time averaging of archaeological shells and then estimates sea-surface temperatures (SSTs) from the oxygen isotopes of selected specimens. Thirty-four radiocarbon-dated shells exhibited significant time averaging between 310 to 1170 yr that could not be explained by analytical error alone. This finding illustrates the need for individually dating shells in future paleoclimate investigations aiming for high temporal resolution. Nine isotopically analyzed shells dated to the Neolithic phase, between 5700 and 7600 cal yr BP, indicate that assuming constant oxygen isotopes of seawater, SSTs remained consistently warm, between 20°C and 22°C, that is, 2°C–4°C warmer than today. Results point to warmer conditions during the Neolithic, supporting the hypothesis that the rise of a food production mode of life in NE Morocco could have in part been triggered by warming conditions following the colder 8.2 event.